Adiponectin Regulates Bone Marrow Mesenchymal Stem Cell Niche Through a Unique Signal Transduction Pathway: An Approach for Treating Bone Disease in Diabetes. (18th December 2014) - Yu, Liming; Tu, Qisheng; Han, Qianqian; Zhang, Lan; Sui, Lei; Zheng, Leilei; Meng, Shu; Tang, Yin; Xuan, Dongying; Zhang, Jin; Murray, Dana; Shen, Qingping; et al.
Abstract: Adiponectin (APN) is an adipocyte-secreted adipokine that exerts well-characterized antidiabetic properties. Patients with type 2 diabetes (T2D) are characterized by reduced APN levels in circulation and impaired stem cell and progenitor cell mobilization from the bone marrow for tissue repair and remodeling. In this study, we found that APN regulates the mobilization and recruitment of bone marrow-derived mesenchymal stem cells (BMSCs) to participate in tissue repair and regeneration. APN facilitated BMSCs migrating from the bone marrow into the circulation to regenerate bone by regulating stromal cell-derived factor (SDF)−1 in a mouse bone defect model. More importantly, we found that systemic APN infusion ameliorated diabetic mobilopathy of BMSCs, lowered glucose concentration, and promoted bone regeneration in diet-induced obesity mice. In vitro studies allowed us to identify Smad1/5/8 as a novel signaling mediator of APN receptor (AdipoR)−1 in BMSCs and osteoblasts. APN stimulation of MC3T3-E1 osteoblastic cells led to Smad1/5/8 phosphorylation and nuclear localization and increased SDF-1 mRNA expression. Although APN-mediated phosphorylation of Smad1/5/8 occurred independently from adaptor protein, phosphotyrosine interaction, pleckstrin homology domain, and leucine zipper containing 1, it correlated with the disassembly of protein kinase casein kinase 2 and AdipoR1 in immunoprecipitation experiments. Taken together, this study identified APN as a regulator of BMSCs migration in response to bone injury. Therefore, our findings suggest APN signaling could be a potential therapeutic target to improve bone regeneration and homeostasis, especially in obese and T2D patients. Stem Cells 2015;33:240–252